1999
DOI: 10.1002/jlb.66.4.588
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of cytokine signaling (SOCS): negative regulators of signal transduction

Abstract: SOCS-1 was originally identified as an inhibitor of interleukin-6 signal transduction and is a member of a family of proteins (SOCS-1 to SOCS-7 and CIS) that contain an SH2 domain and a conserved carboxyl-terminal SOCS box motif. Mutation studies have established that critical contributions from both the amino-terminal and SH2 domains are essential for SOCS-1 and SOCS-3 to inhibit cytokine signaling. Inhibition of cytokinedependent activation of STAT3 occurred in cells expressing either SOCS-1 or SOCS-3, but u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 22 publications
2
66
0
Order By: Relevance
“…Cell adhesion molecule gene Icam1 was more highly expressed in ATM-1-infected mice, and this receptor is associated with leukocyte migration. ATM-1 induced higher expression of genes that regulate inflammation, including Nfkbia, Atf3, Socs3, and zinc finger proteins tristertrapolin (Zfp36) and Zc3h12a, which destabilize mRNA transcripts of proinflammatory cytokines (30)(31)(32)(33). This is consistent, because during activation of inflammation there is also concomitant negative regulation that dampens the immune response and aids in resolution of inflammation.…”
Section: Cellular Infiltration and Changes In Host Gene Expression Immentioning
confidence: 75%
“…Cell adhesion molecule gene Icam1 was more highly expressed in ATM-1-infected mice, and this receptor is associated with leukocyte migration. ATM-1 induced higher expression of genes that regulate inflammation, including Nfkbia, Atf3, Socs3, and zinc finger proteins tristertrapolin (Zfp36) and Zc3h12a, which destabilize mRNA transcripts of proinflammatory cytokines (30)(31)(32)(33). This is consistent, because during activation of inflammation there is also concomitant negative regulation that dampens the immune response and aids in resolution of inflammation.…”
Section: Cellular Infiltration and Changes In Host Gene Expression Immentioning
confidence: 75%
“…54 The suppressors of cytokine signaling-1 (SOCS-1) and SOCS-3 are regulatory proteins involved in terminating IL-6 signaling by inhibiting the JAK/STAT pathway. 55 SOCS-1 expression is increased by IL-6 in prostate cancer cell lines, and it has been shown that SOCS-1 has a growth-inhibitory effect in these cells. SOCS-1 down-regulation did not, however, prevent IL-6 induced growth inhibition of LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%
“…EF/BOS plasmids expressing SOCS-1, SOCS-2, SOCS-3, and CIS were obtained from Dr. Tracy A. Willson (35). As baits for the yeast two-hybrid assay, corresponding DNA fragments were amplified by PCR with Pyrobest enzyme (Takara) using primers with EcoRI (5Ј-primer) or BamHI (3Ј-primer) site extension.…”
Section: Methodsmentioning
confidence: 99%
“…SOCS-6 and deletion mutants were synthesized in the presence of [ 35 S]methionine using TNT T7-quick coupled transcription/translation kit (Promega). 35 SLabeled proteins were mixed with immobilized GST or GST fusion protein in 1 ml of binding buffer (phosphate-buffered saline containing 0.25% Nonidet P-40) and incubated at 4°C for 1 h. After five washes with 1 ml binding buffer, bound proteins were eluted with SDS sample buffer, separated on 4 -20% SDS-PAGE, and analyzed by autoradiography.…”
Section: Methodsmentioning
confidence: 99%